Patent Protection Regulations in Indonesia - Martinelli, Imelda; Samuel, Christian; Howard, Christopher (CV. Rayyan Dwi Bharata, 2023)
Intellectual property rights are one of the most important things in the business world. One of the striking parts of intellectual property rights is patents related to inventions in technological developments which are very important nowadays considering the existence of strong technological developments. In relation to patents, what is striking is the protection of patents currently in effect in Indonesia. Basically, this has been regulated in Law Number 13 of 2016 concerning Patents.